2019
DOI: 10.3390/plasma2030029
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Influence of Target Physical Properties on an Impinging Plasma Jet

Abstract: The present work aims to investigate the interaction between a plasma jet and targets with different physical properties. Electrical, morphological and fluid-dynamic characterizations were performed on a plasma jet impinging on metal, dielectric and liquid substrates by means of Intensified Charge-Coupled Device (ICCD) and high-speed Schlieren imaging techniques. The results highlight how the light emission of the discharge, its time behavior and morphology, and the plasma-induced turbulence in the flow are af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…It has been reported that the surface of treatment can greatly affect plasma discharge. [13,28] Lin et al [13] and Simoncelli et al [28] have shown that electrical power is higher for plasma discharges on metal compared to a dielectric for both DBDs and plasma jets, respectively. As plasma treatments in this study for all chemical and biological analyses were performed in polystyrene well plates, the energy per pulse of DBD plasma was calculated in a setting that closely resembles these experiments (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the surface of treatment can greatly affect plasma discharge. [13,28] Lin et al [13] and Simoncelli et al [28] have shown that electrical power is higher for plasma discharges on metal compared to a dielectric for both DBDs and plasma jets, respectively. As plasma treatments in this study for all chemical and biological analyses were performed in polystyrene well plates, the energy per pulse of DBD plasma was calculated in a setting that closely resembles these experiments (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive discussion on these topics can be found in 13 16 . The influence of the target characteristics on the plasma behaviour is most easily observed through fast imaging of the discharge and gas flow visualization 17 . To understand the electron dynamics more advanced diagnostics are required.…”
Section: Introductionmentioning
confidence: 99%
“…As the plasma-liquid chemistry is of less importance, also short-lived species such as superoxide and hydroxyl radicals, that would rapidly deteriorate under in vitro culture conditions before reaching the cells, have to be taken into account 46 . Other parameters, such as electric fields, investigated as a mechanism contributing to plasma medicine effects [90][91][92] , might also be considered to explain the differences.…”
Section: Discussionmentioning
confidence: 99%